Electrochemically controlled cocrystallisation of caffeine:1-hydroxy-2-naphthoic acid. Issue 1 (10th December 2021) - Kaliszczak, Magdalena; Durand, Pierrick; Wenger, Emmanuel; Dossot, Manuel; Jones, Franca; Arrigan, Damien W. M.; Herzog, Grégoire
Abstract : The formation of caffeine and 1-hydroxy-2-naphtoic acid cocrystals at a water–oil interface was controlled by potential difference, Δwo ϕ, favouring one polymorphic form of the cocrystal. Abstract : Controlled formation of cocrystals is an important objective in drug development. Here, cocrystallisation of caffeine and 1-hydroxy-2-naphthoic acid was investigated at the interface between two immiscible electrolyte solutions under chemical polarisation. In this way, selective cocrystallisation was achieved, as verified by X-ray diffraction and Raman spectroscopy. Positive interfacial potentials favoured the formation of one polymorphic form of caffeine:1-hydroxy-2-naphthoic acid cocrystal. This approach to electrochemically controlled cocrystallisation opens up new possibilities for drug development.